Quand Ça Fait Si Mal: Protestation, Subversion et Espérance Dans le Psaume 137 - Sanon, Yacouba (Old Testament Essays, 2020)
This article examines Psalm 137 in the light of reggae songs by two Ivorian Rastas. The main objective is to demonstrate that the Psalm participates in the construction of a subversive identity by insisting on the transformative power of lament and collective memory. The article is arranged into three main sections: (1) the socio-historical context of the birth of Psalm 137; (2) the literary and canonical context; and (3) socio-theological and comparative analysis. The comparative reading of the different texts makes it possible to highlight the subversive and protest character of Psalm 137. It also makes it possible to highlight the need for reflection on the past, the value of decision making in the present and the need to desire a future built on justice. https://doi.org/10.17159/2312-3621/2020/v33n3a13